PENGARUH KETINGGIAN TEMPAT DAN KEMIRINGAN LERENG TERHADAP PRODUKSI KARET (Hevea brasiliensis Muell. Arg.) DI KEBUN HAPESONG PTPN III TAPANULI SELATAN - Andrian Andrian; Supriadi Supriadi; Purba Marpaung (Universitas Sumatera Utara, 2014)
The elevation and slope effect significantly to growth and rubber (Hevea brasiliensis Muell. Arg.)production . This research was done in Hapesong Farm, Batang Toru sub-district in July – August2013. The aim of this research is to know the effect of elevation and slope on rubber production inHapesong Farm. The sampling used free survey method and Geographic Informatin Systems (GIS).The variables are elevation and slope, and then analysed by regretion method.The result showedthat elevation, slope is significant to decrease the rubber production, but jointly elevation and slopedo not. Elevation of the best places in the study area is 84.5 meters above sea level. The land on theelevation 294.5 meters above sea level, preferably the rubber is not planted anymore.Keyword: elevation, slope, rubber